COVID-19 pandemic in low-risk pregnant women in 2020-2022: disease confounders and clinical characteristics - T. E. Belokrinitskaya; N. I. Frolova; K. A. Kargina; E. A. Shametova; M. I. Chuprova; K. A. Rodionova (Фундаментальная и клиническая медицина)
Aim. To identify confounders and clinical symptoms of COVID-19 in low-risk pregnant women during the pandemics from 2020 to 2022.Materials and Methods. The study included pregnant women with COVID-19: 1) those who have been admitted in October-December 2020 (n = 163); 2) those who have been admitted in May-August 2021 (n = 158); 3) those who have been admitted in January-February 2022 (n = 160). Patients in all groups were in the 3st trimester of gestation and were comparable in age (18–35 years), socioeconomic status, parity, body mass index, and had no established risk factors for COVID-19.Results. Iron deficiency anemia, tobacco smoking, and belonging to the East Asian ethnic group were recognized as reliable confounders for COVID-19 in pregnant women. In the 1st year of the pandemic, the most common symptoms were: loss of smell/taste (87.7%), somnolence (68,7%), and shortness of breath (68.1%). In the 2nd pandemic year, SARS-CoV-2 Delta variant more frequently resulted in fever above 38°C (19.6% vs 7.4%), pneumonia (61.4% vs 21.4%), respiratory failure (17.7% vs 4.9%), admission to intensive care unit (11.4% vs 6.4%), and invasive mechanical ventilation (1.89% vs 0). Symptoms of COVID-19 in the 3rd year of the pandemic were similar to those observed in seasonal acute respiratory viral infections: runny nose (66.7%) and cough (54.4%), whereas the cases of pneumonia were rare (3.8%).Conclusion. Among the most reliable confounders of COVID-19 in pregnant women without any risk factors in the 3rd trimester of gestation are iron deficiency anemia, tobacco smoking, and belonging to the East Asian ethnic group. Each SARS-CoV-2 variant provoked vastly different symptoms.